DESIGN AND IMPLEMENTATION OF VESSEL CUTTING SIMULATION USING SOFA FRAMEWORK - INDRIANI (NIM : 23208349); Pembimbing I : Dr. Ir. Aciek Ida W.; Pembimbing II : Dr. Ir. Yudi, GINA
Cabbage Simulator is a medium of learning of coronary heart surgery with virtual reality concept. By using the finite element approach and changing the topology of the SOFA, developed a simulation of the cutting of blood vessels to improve the design of simulators Cabbage. In the simulation, will be shown the process of cutting the blood vessels are then transplanted into a clogged artery in the heart. The design of the cutting simulation begins with the determination of blood vessel movement trajectory of the blade on the cutting area, the determination of the collision detection points using the distance formula to the field, the removal of tetrahedral mesh when it comes in contact with Topology Mapping, until the vessel cutted. The results obtained show that the implementation meets the cutting simulation, mathematical models have been designed so that the system can be applied to existing products. But not yet able to display realistic visualization.